Exploring the Role of Homeopathy in Managing Guillain-Barré Syndrome: An Integrative Approach (Homoeopathy for All, 2025)
Guillain-Barré Syndrome (GBS) is a rare but serious autoimmune  disorder where the body’s immune  system mistakenly attacks the  peripheral nervous system. This  results in inflammation of the nerves,  leading to symptoms such as muscle  weakness, tingling, and numbness,  which may progress to paralysis in  severe cases.
Keywords: peripheral; system